1998
DOI: 10.1161/01.hyp.31.4.896
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Association of M235T Polymorphism in Angiotensinogen Gene and Diabetic Nephropathy in NIDDM

Abstract: Abstract-This study examined the association between the development of nephropathy in non-insulin-dependent diabetes mellitus (NIDDM) patients and M235T polymorphism in the angiotensinogen gene. White NIDDM patients with diabetic nephropathy (case subjects, nϭ117) and patients without any evidence of nephropathy and Ն10 years of NIDDM (control subjects, nϭ125) were selected from among patients of the Joslin Diabetes Center and examined. In addition to a standardized examination, blood was drawn for DNA and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 28 publications
3
24
0
Order By: Relevance
“…The M235T polymorphism of the AGT gene was originally reported to be associated with hypertension (Jeunemaitre et al 1992), and the TT genotype of this polymorphism was also shown to confer a risk for the progression of diabetic nephropathy (Freire et al 1998). However, another study failed to identify the distinct role of the AGT gene in conferring susceptibility to the disease (Zychma et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The M235T polymorphism of the AGT gene was originally reported to be associated with hypertension (Jeunemaitre et al 1992), and the TT genotype of this polymorphism was also shown to confer a risk for the progression of diabetic nephropathy (Freire et al 1998). However, another study failed to identify the distinct role of the AGT gene in conferring susceptibility to the disease (Zychma et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For example, diabetic foot lesion has a poorer prognosis in men than in women (20). The DNA polymorphism that promotes angiotensinogen gene expression increases the risk of nephropathy in diabetic men but not women (21). The risk of cardiovascular disease is higher in diabetic women than in men (22).…”
Section: Lung Volumementioning
confidence: 98%
“…More than 30 AGT genetic variants have been described so far (63,64) and one of them, a T to C base substitution at position 702 on exon 2 with consequent replacement of methionine 235 with threonine (M235T), has been associated with arterial hypertension (63), and with progression of diabetic nephropathy (65,66). Actually, the possibility that different AGT genotypes might result in different AGT bioavailability raised the intriguing hypothesis that RAS activity might be affected not only by ACE I/D genotypes but also by the several variants of the AGT gene.…”
Section: Other Ras Polymorphisms and Their Interactions With The Ace mentioning
confidence: 99%